Ο οικουμενικός πατριάρχης Άγιος Αθανάσιος Α’ και η διδασκαλία του προς τους κατοίκους της Μικράς Ασίας κατά το 1303 - Καλομοιράκης Δημήτρης Εμμ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
The Patriarch of Constantinople Athanasios I, who was later on canonized by the Church, was born c. 1235 at Adrianople. As a novice on Mount Athos he was a disciple of Nicephorus the Hesychast. He died in Constantinople between 1310 and 1323. Although a number of biographical details have survived and a few studies have been recently devoted to the subject, the life and teaching of Saint Athanasios have come down to us marred by confusion and contradictions. The simplicity and austerity of his character annoyed his contemporary historians and officials who as a rule have judged him with severity. His determination regarding the literal application of scriptural and patristic teaching, provoked many adverse reactions as well among the clergy and hierarchy. Patriarch Athanasios I in collaboration with Emperor Andronicus II (1282- 1328) worked for the restoration of the ecumenicity of the patriarchate through the strengthening of Orthodox tradition and faith. Te emperor employed the patriarch’s appeals for «return to the faith» and «repentence» as the axis of a policy which tended to empower Sacerdotium rather than Imperium in the Byzantine domains. Andronicus’s policy, which as a rule was carried on by his successors, secured the survival of the Orthodox flock, regardless of ethnic origin, even after the fall of Constantinople. The patriarch’s interest was not limited to the Orthodox of the empire but it extended to other Orthodox nations as well, including the Russians. The spiritual and cultural flowering of the Paleologan period, conventionally known as the «Paleologan Renaissance» could be seen as the outcome of the restoration of Orthodoxy by Andronicus II and Athanasius I, rather than as a reorientation toward classical Greek antiquity. The present paper, after a survey of the life and work of Saint Athanasios, publishes for the first time the complete text of a letter by the Patriarch addressed to the Christian inhabitants of Asia Minor. The text is transmitted by Codex Vaticanus Grecus 2219. Three important pieces of information are contained in this text, which appears on fols. 230r-232r of the Codex. First the teaching is dated to the Saint’s second patriarchate (after June 23, 1303), probably in July 1303. The Saint explains the reasons which led him to accept the patriarchate for a second time. Secondly the text describes in dramatic terms the living conditions of the Christian population of Asia Minor. The patriarch does not fail to point at the causes of these calamities. Finally the patriarch calls upon the population of Asia Minor to close ranks and be ready for action and hints at the imminent mission of an imperial envoy to whom they were expected to show obedience and submission in order to be redeemed. The new text makes possible a new dating for another previously published letter by the Patriarch from the same Codex (fols. 17r-17v), which must now be redated not before the Spring but before the Autumn 1303, probably in August of that year. In that letter the patriarch criticised the emperor’s intention to deliver the defense of Asia Minor to Western warriors, apparently Catalans. The identity in content and attitude between the two letters dictates their dating before September 1303, when the Catalans arrived in Asia Minor. The great value of both texts from a historical point of view consist in the information they supply on conditions in Asia Minor and on the state of mind of the local inhabitants, while on the other hand they reveal clearly the prophetic stature of the patriarch, his pastoral concern for his flock and his active involvement in public affairs.